Health impact assessment concepts, theory, techniques, and applications - Kemm, John.; Parry, Jayne; Palmer, Stephen R. (Oxford : Oxford University Press, 2004)
Providing a comprehensive overview of the concepts, theory, techniques and applications of Health Impact Assessment to aid all those preparing projects or carrying out assessments, this book draws on examples and thinking from many different disciplines and many parts of the world.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Health risk assessment